A data driven fault isolation method based on reference faulty situations with application to a nonlinear chemical process - Ragot, José; Mourot, Gilles; Kallas, Maya (Zielona Góra: Uniwersytet Zielonogórski)
The diagnosis of systems is one of the major steps in their control and its purpose is to determine the possible presence of dysfunctions, which affect the sensors and actuators associated with a system but also the internal components of the system itself. On the one hand, the diagnosis must therefore focus on the detection of a dysfunction and, on the other hand, on the physical localization of the dysfunction by specifying the component in a faulty situation, and then on its temporal localization.
Keywords: fault detection; fault isolation; prediction; nonlinear systems; data modelling; kernel